Por trás e para além dos muros: tensões, contradições e desafios no cotidiano de trabalhadores da socioeducação a partir da política do SINASE - Mella, Lisiane Ligia (2017)
This study contemplates the subject of socioeducation, a public policy aimed at adolescents in conflict with the law, and had as objective to analyze how the workers of the socioeducation perceive their relation with the adolescent in conflict with the law, the socioeducative system and the conduction of the work developed since the advent of Law 12.594/12, called as "SINASE‟s law". This law was promulgated in the year 2012 by the Presidency of the Republic and instituted the National System of Socio-educational Attendance - SINASE, whose purpose is to regulate the service to the adolescent that is fulfilling socio-educational measures. The study is descriptive and has a qualitative design, being used as a data collection instrument a semi-structured interview directed to managers, members of the technical team and socioeducator agents working in a socioeducative unit, totalizing twelve participants. The theoretical basis of the research is interlaced with the speeches of the participants, composing empirical experiences that constituted and delineated different political and pedagogical perspectives, projects and postures, presenting the tensions, conflicts and contradictions present in the daily life of these workers and the dynamics that involve being "inside" and "outside" the walls surrounding the socio-educational unit and also the socio-educational system. The initial chapters contemplates the theoretical foundations that underpin socioeducation, including social education, non-formal education and Makarenkian pedagogy. Next, basic elements of the policies of attention to adolescents in conflict with the law are presented, through the contributions of authors such as Irene Rizzini, Francisco Pilotti, Michel Foucault and Arno Vogel. For the analysis of the scenario of social inclusion of adolescents in conflict with the law, references were authors such as François Dubet and Carmem Silveira de Oliveira. The text follows with the exposition of the brazilian context in the perspective of Jessé de Souza, Mione Apolinário Sales and Loic Wacquant, including the understanding of the complex processes of exclusion, domination and the reproduction of violence. Based on the presentation of the scenarios involving adolescents in conflict with the law and the delimitations of the SINASE‟s law, the several dilemmas experienced by the participants in the research with the arrival of the law in the socio-educational are recomposed, especially in the sudden form as it was inserted in the work routine. In the absence of a dialogue involving all workers, difficulties appeared regarding the full comprehension of the meanings of the SINASE‟s law, opening space for subjective interpretations, especi ally regarding the disciplinary regimes applied to adolescents. With the analysis of the data, two pedagogical actions developed by the workers in the daily routine with the adolescents were identified: one turns to the need to work with the adolescents from rules and delimited norms; and another, the need to work with adolescents from listening and talking. Such actions and pedagogical positions reveal distinct realities and discourses, establishing and fostering tensions among work colleagues. The research participants also highlighted challenges arising from work in social education, including the lack of recognition and "unity" among workers, including pressure and illness as manifestations of suffering. The study allows to affirm that looking back to the workers of the socioeducation requires immersing in this reality from the perspective of those who accompany the adolescent directly and passing through the socioeducational system, contributing to the promotion and expansion of spaces for listening, dialogue and reflection.